Diseño arquitectónico del Palacio Municipal del Gobierno Autónomo Descentralizado del cantón Salitre implementando criterios de eficiencia energética y funcionalidad - Torres Moreta, Johnny Ricardo (2025)
The architectural design project for the Municipal palace of the Decentralized Autonomous Government of Salitre emerges as a comprehensive solution to strengthen public infrastructure, ensuring an efficient and functional spatial organization. This proposal aims to consolidate all administrative departments into a single building, optimizing operations and promoting a more agile and coordinated institutional management. The facility's planning adheres to energy efficiency, sustainability, and structural resilience criteria, ensuring high performance with benefits for both the administration and the community. Currently, the dispersion of municipal offices generates high operational costs due to the leasing of external spaces, limiting the efficient management of resources. The construction of the new Municipal Palace will significantly reduce these expenses by centralizing institutional activities in an environment designed to enhance interdepartmental communication and public service. Strategic areas such as administrative offices, auditoriums, meeting rooms, and spaces for citizen interaction have been planned, fostering more transparent and inclusive governance.